‘Beyond Cancer’: a study protocol of a multimodal occupational rehabilitation programme to support breast cancer survivors to return work - Sheppard, D.M.; Frost, D.; Jefford, M.; O'Connor, Moira; Halkett, Georgia (BMJ PUBLISHING GROUP, 2019)
Introduction: With more women working and surviving breast cancer, issues concerning sustainable employment must be addressed. Support to transition back to work is a gap in survivorship care. This paper describes the feasibility trial protocol for a 'Beyond Cancer', a multimodal occupational rehabilitation programme to support breast cancer survivors' return to work. Breast cancer survivors are hypothesised to show improved work status, work capacity and perceived support at work at 6 months postintervention relative to baseline and a historical usual care group.